2008
DOI: 10.1623/hysj.53.4.741
|View full text |Cite
|
Sign up to set email alerts
|

Source areas and mixing of runoff components at the hillslope scale—a multi-technical approach

Abstract: Hillslope processes (i.e. water flow pathways, source areas and residence times) are essential for predicting water quantities and water quality. A multi-technical approach using classical hydrometry, natural and artificial tracers and electrical resistivity tomography (ERT) was applied to two adjacent steep hillslopes in the Black Forest Mountains, Germany. The differences in the hydrological and hydrochemical responses during three floods were larger than expected based on previously available information of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 22 publications
3
43
0
1
Order By: Relevance
“…There was little evidence of non-conservative behaviour of the geochemical tracers (Uhlenbrook et al, 2002;Asano et al, 2003) in the first ∼5-6 h after the beginning of the event as the event/pre-event estimates of both EC and SiO 2 give generally similar results, although it is frequently assumed that they have different timescales of non-conservative behaviour (e.g. Laudon and Slaymaker, 1997;Uhlenbrook et al, 2002;Asano et al, 2003;Pellerin, 2007), which would imply consistently different event/pre-event contribution estimates.…”
Section: Mataini Catchment (03 Km 2 )mentioning
confidence: 97%
See 4 more Smart Citations
“…There was little evidence of non-conservative behaviour of the geochemical tracers (Uhlenbrook et al, 2002;Asano et al, 2003) in the first ∼5-6 h after the beginning of the event as the event/pre-event estimates of both EC and SiO 2 give generally similar results, although it is frequently assumed that they have different timescales of non-conservative behaviour (e.g. Laudon and Slaymaker, 1997;Uhlenbrook et al, 2002;Asano et al, 2003;Pellerin, 2007), which would imply consistently different event/pre-event contribution estimates.…”
Section: Mataini Catchment (03 Km 2 )mentioning
confidence: 97%
“…Uhlenbrook et al, 2002), was previously shown to behave nonconservatively. However, the timescales at which the tracer compositions, i.e.…”
Section: End-membersmentioning
confidence: 99%
See 3 more Smart Citations